Análise da falta de fiscalização do greenwashing como prática da falsa sustentabilidade e seus efeitos na vida dos consumidores da Zona Leste de São Paulo nos últimos 5 anos - SANTOS, Bruna Eustachio dos; BARBOZA, Larissa Lemos; MENDES, Maria Clara Ramos; FRANZINI, Mayara Saldanha; OLIVEIRA, Nathalia Silva de; SOARES, Vitor Hugo Albuquerque; RODRIGUES, Vitória Alves (285, 2024)
O tema abordado é de extrema importância, pois analisa a situação dos impactos ambientais nas empresas e motiva a busca para os efeitos da falsa sustentabilidade que na prática causa diversos efeitos no cotidiano dos consumidores da Zona Leste de São Paulo perante os últimos cinco anos. O Greenwashing (lavagem verde), é a divulgação de informações falsas, enganosas ou incompletas sobre sustentabilidade transpassadas da empresa para os clientes. Com o aumento das pautas ambientais no mercado, as empresas buscam por estratégias de marketing que transpareçam uma imagem limpa e sustentável para que sua reputação seja melhor entre os consumidores, sem de fato aplicá-las em seu negócio.

Since the mid-1960s, the word “sustainability” has been gaining more visibility each day. Concern for the environment has become increasingly necessary as the years go by. As certain issues grow in prominence, it is natural for industries and companies to adapt to them, in order to showcase a competitive edge to society and attract those consumers who are engaged in the cause and prefer sustainable products, even if they are more expensive. However, there are also companies that appropriate the topic solely for profit, and this is what the present study is based on. The subject is of utmost importance as it analyzes the situation of environmental impacts on companies and motivates the investigation into the effects of false sustainability, which in practice, cause various effects on the daily lives of consumers in the East Zone of São Paulo over the past five years. Greenwashing is the dissemination of false, misleading, or incomplete information about sustainability transmitted by companies to their customers. With the rise of environmental issues in the market, companies seek marketing strategies that project a clean and sustainable image to improve their reputation among consumers, without actually implementing such practices in their business. This practice, besides being an immoral act toward customers, is a strong factor for the company to lose its credibility in the market if discovered. Furthermore, the article seeks to understand and expose the occurrence of these practices, aiming to raise awareness and promote an understanding of the seriousness and consequences involved.
Keywords: Sustentabilidade; Consumo; Marketing; Marketing ambiental; Consumidor; Gestão e Negócios